2006
DOI: 10.3109/s10165-006-0525-z
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effects of hepatocyte growth factor on scleroderma fibroblasts and analysis of its mechanism

Abstract: We investigated the effect of hepatocyte growth factor (HGF) on collagen metabolism in cultured fibroblasts from scleroderma (SSc) patients and discussed the possible mechanism of its effect. Synthesis of matrix metalloproteinase-1 (MMP-1) and collagen and mRNA levels of various cytokines were examined by enzyme-linked immunosorbent assay and real-time polymerase chain reaction, respectively. Hepatocyte growth factor enhanced MMP-1 production and mRNA levels of MMP-1 and Ets-1 (a transcriptional factor of MMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…Basal expression and activity of MMP-1 in SSc lung fibroblasts is reduced compared with that of normal fibroblasts (26). It has been reported that HGF induces expression and activity of MMP-1 in SSc skin fibroblasts (20,21). To examine whether HGF affects MMP-1 expression in SSc lung fibroblasts, we incubated cells with various concentrations of HGF (5-500 ng/ml) for 72 hours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basal expression and activity of MMP-1 in SSc lung fibroblasts is reduced compared with that of normal fibroblasts (26). It has been reported that HGF induces expression and activity of MMP-1 in SSc skin fibroblasts (20,21). To examine whether HGF affects MMP-1 expression in SSc lung fibroblasts, we incubated cells with various concentrations of HGF (5-500 ng/ml) for 72 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past several years, progress has been made in identifying the cellular targets of HGF and in unraveling the molecular mechanisms that underlie its action in tissue fibrosis (13,14,16,17,21). The biologic effects of HGF are mediated by a membrane-spanning c-Met tyrosine kinase receptor (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HGF has been shown to attenuate CTGF expression and collagen accumulation in several murine models of fibrosis (23,35). Recently, several groups of investigators reported that HGF inhibits collagen and CTGF production in skin fibroblasts from SSc patients (14,36,37). To establish whether recombinant HGF affects the accumulation of collagen and CTGF in human lung fibroblasts in the same way as in skin fibroblasts, we measured collagen and CTGF expression in lung fibroblasts isolated from Caucasian and African American SSc patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ets-1 is activated in VSMCs by a variety of stimuli including platelet-derived growth factor-BB, interleukin-1, and tumor necrosis factor-␣ (14,30,48,60). Increased expression of various proteases that degrade the ECM was reported in Ets-1-overexpressing cells (7,16,20,51,54). However, the involvement of Ets-1 in EGF-induced MMP-1 and -9 expressions in carotid plaque VSMCs are not known.…”
Section: Discussionmentioning
confidence: 99%